Evaluation of dietary vitamin C supplementation on growth performance and oxidative responses of pacific whiteleg shrimp juvenile Litopenaeus vannamei Boone - Ratnawati Rifai; Asrianti Sani; Fauziah Nurdin; Bustamin Bustamin; Rahmadina Rahmadina (Indonesian Society of Scientific Aquaculture (ISSA), 2026)
Vitamin C cannot be synthesized by shrimp and must be obtained from dietary sources; however, its supply through feed is often insufficient. This study aimed to evaluate the growth performance and oxidative response of juvenile whiteleg shrimp (Litopenaeus vannamei) supplemented with dietary vitamin C. Juvenile shrimp at the PL-25 stage, acclimated to a salinity of 20 ppt, were stocked into 16 rearing containers, each filled with 40 L of seawater from a total 250 L fiberglass tank. Each container contained 20 juveniles with an initial average body weight of 0.001 g per individual. The rearing period lasted 60 days, during which shrimp were fed three times daily. The feeding rate (FR) was initially set at 11% of body weight for the first 30 days and then reduced to 7% thereafter. The experimental design followed a completely randomized design (CRD) consisting of four treatments and four replicates: A (0 mg/kg), B (150 mg/kg), C (300 mg/kg), and D (450 mg/kg) of dietary vitamin C supplementation. The results showed that supplementation of vitamin C at 300 mg/kg diet produced the best growth performance (RGR, PER, FCR) and survival rate, which were positively correlated with SOD enzyme activity. The oxidative response parameters (HSI and MDA) showed the lowest values in this optimal treatment. The highest growth performance was obtained from the treatment with 300 mg vitamin C/kg diet, achieving a relative growth rate of 4,358.6%, the lowest MDA concentration of 3.58 ± 0.37 nmol/L, and the highest SOD activity of 88.35 ± 2.22 U/mL enzyme. Keywords: growth, oxidative responses, shrimp, vitamin C Abstrak Vitamin C tidak dapat disintesis oleh udang, zat ini dapat diperoleh dari pakan namun pasokannya masih belum mencukupi. Tujuan dari penelitian ini untuk menguji kinerja pertumbuhan dan respon oksidatif juvenil udang vaname dengan suplementasi vitamin C dalam pakan. Juvenil udang vaname PL 25, yang telah diadaptasikan di salinitas 20 ppt ditebar pada 16 wadah pemeliharaan yang diisi dengan air laut volume 40 L dari volume total bak fiber 250 L dengan jumlah total juvenil 20 ekor dan rata-rata berat awal juvenile 0,001 g/ekor; waktu pemeliharaan udang;selama 60 hari dengan pemberian pakan tiga kali perhari dan jumlah pakan ditentukan dengan FR 11% dan setelah pemeliharaan 30 hari FR diturunkan menjadi 7%. Rancangan penelitian menggunakan rancangan acak lengkap (RAL) dengan empat taraf perlakuan dan empat ulangan dengan komposisi perlakuan; A (dosis 0 mg/kg), B (dosis 150 mg/kg). C (dosis 300 mg/kg) D (dosis 450 mg/kg). Hasil penelitian menunjukkan bahwa suplementasi vitamin C dosis 300 mg/kg pakan menghasilkan kinerja pertumbuhan (LPR, REP, RKP) dan TKH terbaik dan berkorelasi dengan aktivitas enzim SOD. Hasil uji respons oksidatif (IHS dan MDA) menunjukan hasil terendah pada perlakuan terbaik di penelitian ini. Kinerja pertumbuhan optimal diperoleh dari trreatment 300 mg vitamin C/kg sebesar 4.358.6% dengan nilai MDA terendah 3,58 ± 0,37 nmol/L dan aktivitas SOD tertinggi 88,35 ± 2,22 Unit/mL enzim. Kata kunci: pertumbuhan, respons oksidatif, udang vaname, vitamin C